2018
DOI: 10.1186/s13023-018-0808-4
|View full text |Cite
|
Sign up to set email alerts
|

Less invasive treatment of sleep-disordered breathing in children with syndromic craniosynostosis

Abstract: BackgroundInfants and children with syndromic craniosynostosis (SCS), such as Apert-, Crouzon- or Pfeiffer syndrome, are prone to sleep disordered breathing (SDB) including obstructive sleep apnea and upper airway resistance syndrome (OSAS, UARS), potentially leading to tracheostomy. We modified the Tübingen Palatal Plate (TPP), an oral appliance with a velar extension effectively treating airway obstruction in Robin sequence, by attaching a tube to its velar extension to bridge the narrow pharyngeal airway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The TPP consists of a plate with velar extension that pushes the tongue anteriorly, thereby widening the hypopharynx and releasing the UAO [8]. The effectiveness of this method has been extensively studied in prospective mono-and multicentre studies, in isolated and syndromic RS patients [8][9][10][11] as well as in children with syndromic craniosynostosis and sleep-disordered breathing (SDB) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The TPP consists of a plate with velar extension that pushes the tongue anteriorly, thereby widening the hypopharynx and releasing the UAO [8]. The effectiveness of this method has been extensively studied in prospective mono-and multicentre studies, in isolated and syndromic RS patients [8][9][10][11] as well as in children with syndromic craniosynostosis and sleep-disordered breathing (SDB) [12].…”
Section: Introductionmentioning
confidence: 99%
“…12 This concept has been successfully evaluated in prospective single-center and multicenter studies, both in isolated and syndromic Robin sequence patients 7,11,13,14 and in children with syndromic craniosynostosis and sleep disordered breathing. 15 However, little is known about normal speech development in Robin sequence children. Previous studies presented contradictory results, but most found impaired speech development.…”
mentioning
confidence: 99%
“…12 This concept has been successfully evaluated in prospective single-center and multicenter studies, both in isolated and syndromic Robin sequence patients 7,11,13,14 and in children with syndromic craniosynostosis and sleep disordered breathing. 15…”
mentioning
confidence: 99%